Analyzıng The Needs of ICT-Integrated Englısh Language Teachıng for EFL Learners - Zaki, Leil Badrah; Kaur, Bal Janatte Raj (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2024)
This study aims to know the need for ICT-integrated English language instruction among EFL high school students in the 21st century. It also examines the importance of digital literacy in meeting the educational requirements of learners in the digital age, the concept of a digital learning environment, and its role in developing digital literacy skills. This research applied a mixed-method approach involving qualitative and quantitative data collection techniques. The data were collected from a questionnaire that involved 40 high school students in Batam, Indonesia. The instruments used in collecting the data were observation, questionnaires, and interviews. The findings indicated that students are positive about using ICT in English Language Learning, are satisfied with ICT facilities, and are willing to use it for learning at home. Teachers agree that ICT improves English proficiency but are concerned about time, skills, and support. They also understand the impacts of the media. There is a readiness to embrace digital technologies for education.